A dry electrode membrane and its preparation method and application
Through the dry method electrode method, components such as polymer adhesives and additives are used to prepare dry electrode membranes with high adhesion strength and stability, which solves the low safety performance and insufficient energy density in the traditional wet method. The problem realizes the improvement of battery capacity and cycle stability.
Patent Information
- Application Number
- CN202410062965.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-01-16
AI Technical Summary
The traditional wet coating process produces lithium-ion battery electrodes with low safety performance, complex production, and large waste of energy and resources. At the same time, the electrode active materials are prone to cracking during the preparation process, and the energy density requirements are difficult to meet.
The use of dry electrode method, by mixing the electrode activity materials, auxiliary agents, conductive additives, polymer binders, and set flows according to a specific ratio, heating, extending with polytefluorolytheryne and compounding Attach strength and stability dry method electrode membrane.
Improve the battery capacity and cycle stability, enhance the reversible capacity of the electrode material, avoid the instability of the SEI layer on the electrode surface, and reduce the production cost.
Smart Images

Figure CN117855485B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery energy storage technology, and in particular to a dry electrode method and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in the fields of power energy and electronics due to their high energy density, high conversion efficiency, fast response speed and long cycle life. The electrodes of traditional lithium-ion batteries are prepared by a wet coating process, in which organic solvents are usually used. Most organic solvents have the characteristics of flammability and high toxicity, which greatly reduces the safety performance of lithium-ion batteries. In addition, the residual organic solvents in the electrode preparation process also need to be removed, which makes the wet coating process more complicated, resulting in more energy and resource waste, and the organic solvents are not easy to recycle, which also increases the production cost to a certain extent. In addition, during the volatilization of organic solvents, the electrode active materials are prone to cracking, and the wet coating process often has a low loading amount of electrode active materials, which cannot meet the energy density requirements.
[0003] As a rapidly developing lithium-ion battery preparation technology, the dry process does not require the use of a large amount of organic solvents, or even no organic solvents, and avoids most of the problems of the wet coating process. However, in the preparation of dry electrodes, the binder, as an indispensable part, has always had many problems, and the choice of binder also directly affects the working performance of the prepared battery.
[0004] Therefore, an efficient binder becomes an important task in the research of dry electrodes. Summary of the invention
[0005] In order to solve the above-mentioned technical problems existing in the prior art, the present application provides a dry electrode method and a preparation method and application thereof.
[0006] In order to achieve the above purpose, the technical solution of the embodiment of the present application is:
[0007] The first aspect of the present application provides a dry electrode membrane, comprising an electrode active material, an auxiliary agent, a conductive additive, a polymer binder and a current collector;
[0008] The polymer adhesive includes polytetrafluoroethylene and polyethylene, and the polyethylene includes at least one of low-density polyethylene, high-density polyethylene and ultra-high molecular weight polyethylene;
[0009] The auxiliary agent includes at least one of a siloxane crosslinking agent and carboxyl cellulose;
[0010] The current collector comprises at least one of a carbon-coated aluminum foil and a carbon-coated copper foil;
[0011] The electrode active material includes at least one of a positive electrode active material and a negative electrode active material. In combination with the first aspect, preferably, the mass ratio of the polytetrafluoroethylene to the polyethylene is 1:0.5-3.
[0012] In combination with the first aspect, preferably, in terms of mass percentage, the electrode active material is 80-85wt%, the conductive additive is 5-10wt%, the polymer binder is 0.5-6wt%, the siloxane crosslinker is 0-5wt%, and the carboxyl cellulose is 0-5wt%;
[0013] And / or, the siloxane crosslinking agent includes one or more of bis[(3-methyldimethoxysilyl)propyl]polyoxypropylene, octamethylcyclotetrasiloxane and polyalkyltriethoxysiloxane.
[0014] In combination with the first aspect, preferably, the carboxycellulose includes one or more of carboxymethyl cellulose, carboxyethyl cellulose, carboxypropyl cellulose, carboxymethyl ethyl cellulose, carboxypropyl methyl cellulose, lithium salt, sodium salt and potassium salt.
[0015] In combination with the first aspect, preferably, the positive electrode active material comprises LiCoO 2 、LiMnO 2 、LiNiO 2 、LiFePO 4 、LiMn 2 O 4 、LiNiCoAlO 2 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、LiNi 0.5 Co 0.2 Mn 0.3 O 2 、LiNi 0.6 Co 0.2 Mn 0.2 O 2 and LiNi 0.8 Co 0.1 Mn 0.1 O 2 One or more of the following;
[0016] And / or, the negative electrode active material includes one or more of hard carbon, soft carbon, artificial graphite, natural graphite, mesophase carbon microbeads, and lithium titanate.
[0017] In combination with the first aspect, preferably, the conductive additive includes one or more of carbon nanotubes, acetylene black, Super P, Ketjen black, MXene and graphene.
[0018] The second aspect of the present application provides a method for preparing the dry electrode film according to the first aspect, the preparation method comprising:
[0019] Mixing an electrode active material, an auxiliary agent, a conductive additive and polyethylene to obtain a first mixture;
[0020] heating the first mixture to obtain a heated first mixture;
[0021] mixing the heated first mixture with polytetrafluoroethylene to obtain a second mixture;
[0022] The second mixture is rolled, and a current collector is added for thermal compounding to obtain a dry electrode membrane.
[0023] In combination with the second aspect, preferably, when the first mixture is heated, the heating temperature is 100-150° C.;
[0024] and / or, the heating time is 10-60 min;
[0025] And / or, the thickness of the dry electrode film is 60-150 μm.
[0026] In combination with the second aspect, preferably, when the second mixture is calendered and a current collector is added for thermal compounding, the calendering temperature is 20-120° C.;
[0027] and / or, the thermal compounding temperature is 70-150°C;
[0028] And / or, the thermal compounding time is 5-60 minutes.
[0029] The third aspect of the present application provides a use of the dry electrode membrane described in the first aspect or the dry electrode membrane prepared by the method described in the second aspect in preparing a battery.
[0030] Compared with the prior art, the limited or beneficial effects of the embodiments of the present application include at least:
[0031] The dry electrode membrane provided in the embodiment of the present application adds different types of polyethylene compared to the traditional dry electrode membrane. On the one hand, due to the limited viscoelasticity of polytetrafluoroethylene, it is impossible to ensure sufficient adhesion strength between the active material, the conductive carbon and the current collector. Therefore, after the addition of polyethylene, the active material can be made more stable and complete during the volume expansion / contraction process, thereby improving the battery capacity and cycle stability; on the other hand, since a mixed conductive interface will be formed during the reduction and defluorination reaction of polytetrafluoroethylene, the electronic conductivity of the conductive interface will destroy the stability of the SEI layer. Polyethylene has a fibrillable structure similar to that of polytetrafluoroethylene, and does not contain fluorine atoms in the structure. Therefore, polyethylene has stronger reduction stability and will not destroy the SEI layer on the electrode surface; thirdly, ultra-molecular weight polyethylene has a larger degree of polymerization and a longer polymer chain than polytetrafluoroethylene, which can produce a better adhesion effect on the active material, conductive carbon and the current collector, thereby alleviating the breakage and shedding of the active material during the volume expansion / contraction process, and can effectively improve the battery capacity and cycle stability. In this way, the addition of polyethylene is beneficial to improve the cycle stability of the battery, so that the battery capacity has a higher retention rate during the charge and discharge cycle. At the same time, it also improves the first-cycle specific capacity of the battery, so that the electrode material can achieve a better reversible capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The charge and discharge cycle test diagram of the button-type lithium-ion batteries prepared in Example 1, Example 4 and Comparative Example 1;
[0033] Figure 2 The charge and discharge cycle test diagram of the button-type lithium-ion batteries prepared in Example 1, Example 5 and Example 6;
[0034] Figure 3 The charge and discharge cycle test diagram of the button-type lithium-ion batteries prepared in Example 7 and Comparative Example 2; DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings. The described embodiments should not be regarded as limiting the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0036] In the following description, reference is made to "some embodiments", which describe a subset of all possible embodiments, but it is understood that "some embodiments" may be the same subset or different subsets of all possible embodiments, and may be combined with each other without conflict. Unless otherwise defined, all technical and scientific terms used in the embodiments of the present application have the same meaning as those commonly understood by those skilled in the art of the technical field of the embodiments of the present application. The terms used in the embodiments of the present application are only for the purpose of describing the embodiments of the present application and are not intended to limit the present application.
[0037] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.
[0038] It should be noted that all raw materials / reagents in the examples of the present application can be purchased on the market or prepared according to conventional methods well known to those skilled in the art; the term "and / or" in the examples of the present application is only used to describe the association relationship between associated objects, indicating that three relationships may exist, for example, A and / or B means the existence of A alone, B alone, and A and B at the same time, among which A and B can be singular or plural, and the character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0039] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0040] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0041] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0042] Those skilled in the art will appreciate that the numerical ranges in the examples of the present application are to be understood as also specifically disclosing each intermediate value between the upper and lower limits of the range. Each smaller range between the intermediate values in any stated value and stated range and any other stated value or intermediate value in the range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.
[0043] Unless otherwise stated, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art in the field described in the present application. Although the present application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the embodiments or test cases of the present application. All documents mentioned in this specification are generally incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of the present application shall prevail.
[0044] It should be noted that all raw materials and / or reagents in the examples of the present application are purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0045] In a first aspect, an embodiment of the present application provides a dry electrode membrane, comprising an electrode active material, an auxiliary agent, a conductive additive, a polymer binder and a current collector;
[0046] The polymer adhesive includes polytetrafluoroethylene and polyethylene, and the polyethylene includes at least one of low-density polyethylene, high-density polyethylene and ultra-high molecular weight polyethylene;
[0047] The auxiliary agent includes at least one of a siloxane crosslinking agent and carboxyl cellulose;
[0048] The current collector comprises at least one of a carbon-coated aluminum foil and a carbon-coated copper foil;
[0049] The electrode active material includes at least one of a positive electrode active material and a negative electrode active material.
[0050] The dry electrode membrane provided in the embodiment of the present application adds different types of polyethylene compared to the traditional dry electrode membrane. On the one hand, due to the limited viscoelasticity of polytetrafluoroethylene, it is impossible to ensure sufficient adhesion strength between the active material, the conductive carbon and the current collector. Therefore, after the addition of polyethylene, the active material can be made more stable and complete during the volume expansion / contraction process, thereby improving the battery capacity and cycle stability; on the other hand, since a mixed conductive interface will be formed during the reduction and defluorination reaction of polytetrafluoroethylene, the electronic conductivity of the conductive interface will destroy the stability of the SEI layer. Polyethylene has a fibrillable structure similar to that of polytetrafluoroethylene, and does not contain fluorine atoms in the structure. Therefore, polyethylene has stronger reduction stability and will not destroy the SEI layer on the electrode surface; thirdly, ultra-molecular weight polyethylene has a larger degree of polymerization and a longer polymer chain than polytetrafluoroethylene, which can produce a better adhesion effect on the active material, conductive carbon and the current collector, thereby alleviating the breakage and shedding of the active material during the volume expansion / contraction process, and can effectively improve the battery capacity and cycle stability. In this way, the addition of polyethylene is beneficial to improving the cycle stability of the battery, so that the battery capacity has a higher retention rate during the charge and discharge cycle. At the same time, it also improves the first-cycle specific capacity of the battery, so that the electrode material can achieve a better reversible capacity.
[0051] In a specific embodiment, the mass ratio of polytetrafluoroethylene to polyethylene is preferably 1:0.5-3.
[0052] In a specific embodiment, in terms of the mass percentage of the components, the electrode active material of the embodiment of the present application is preferably 80-85wt%, the conductive additive is preferably 5-10wt%, the polymer binder is preferably 0.5-6wt%, the siloxane crosslinker is preferably 0-5wt%, and the carboxyl cellulose is preferably 0-5wt%.
[0053] Among them, when the content of the auxiliary agent is lower than 0.5wt%, the bonding and contact tightness of each component cannot be guaranteed; when the content of the auxiliary agent is higher than 5wt%, it will cause a lower battery capacity, resulting in a lower overall energy density of the battery, and is not conducive to the cycle stability of the battery. When the content of the electrode active material is lower than 80wt%, it will cause the capacity of the battery to decrease, resulting in a lower overall energy density that does not meet the current energy needs; when the content of the electrode active material is higher than 85wt%, it is not conducive to the cycle stability of the battery. When the content of the conductive additive is lower than 5wt%, a complete conductive network cannot be formed, which is not conducive to the transmission of electrons / ions and the capacity of the electrode material cannot be fully utilized; when the content of the conductive additive is higher than 10wt%, it will lead to a lower overall energy density of the battery.
[0054] In a specific embodiment, the siloxane crosslinking agent of the embodiment of the present application is preferably one or more of bis[(3-methyldimethoxysilyl)propyl]polyoxypropylene, octamethylcyclotetrasiloxane and polyalkyltriethoxysiloxane.
[0055] It should be noted that the molecular structure of bis[(3-methyldimethoxysilyl)propyl]polyoxypropylene is shown in Formula 1:
[0056]
[0057] In formula 1, 1≤n≤10.
[0058] It should be noted that the molecular structure of octamethylcyclotetrasiloxane is shown in Formula 2:
[0059]
[0060] It should be noted that the molecular structure of polyalkyltriethoxysiloxane is shown in Formula 3:
[0061]
[0062] In Formula 3, 2≤n≤5, R is an alkyl group having 2 to 8 carbon atoms. For example, R can be one of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, hexyl, heptyl or octyl.
[0063] It should be noted that a siloxane crosslinker is a compound containing silicon-oxygen-silicon bonds in its chemical structure, and crosslinks through the formation of silicon-oxygen-silicon bonds when forming a three-dimensional network structure. Siloxane crosslinkers are generally used as crosslinkers in materials to enhance the performance and stability of the materials. Siloxane crosslinkers mainly play the role of crosslinking and fixing the structure in the electrode membrane. Through the action of the siloxane crosslinker, the various components in the electrode membrane can be effectively connected together to form a more stable and dense structure. In addition, the siloxane crosslinker can also improve the mechanical properties, thermal stability and chemical stability of the electrode membrane, so that the electrode membrane has better durability and stability. At the same time, the siloxane crosslinker can also improve the electrochemical properties of the electrode membrane, such as conductivity and ion selectivity.
[0064] In a specific embodiment, the carboxy cellulose of the embodiment of the present application is preferably one or more of carboxymethyl cellulose, carboxyethyl cellulose, carboxypropyl cellulose, carboxymethyl ethyl cellulose, carboxypropyl methyl cellulose, lithium salt, sodium salt and potassium salt.
[0065] It should be noted that carboxyl cellulose plays the main role of thickening, film-forming, emulsification stabilization and providing a certain rigid structure in the electrode membrane. These effects are crucial to the preparation of high-quality electrode membranes. For example, through the thickening effect of carboxyl cellulose, the fluidity and operability of the membrane can be optimized, and the physical properties and stability of the membrane can be improved. At the same time, carboxyl cellulose can also be compounded with other materials to improve the electrochemical properties and stability of the electrode membrane. In addition, carboxyl cellulose also has good biocompatibility and degradability.
[0066] In a specific embodiment, the positive electrode active material of the present application embodiment is preferably LiCoO 2 、LiMnO 2 、LiNiO 2 、LiFePO 4 、LiMn 2 O 4 、LiNiCoAlO 2 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、LiNi 0.5 Co 0.2 Mn 0.3 O 2 、LiNi 0.6 Co 0.2 Mn 0.2 O 2 and LiNi 0.8 Co 0.1 Mn 0.1 O 2 One or more of the .
[0067] In a specific embodiment, the negative electrode active material of the embodiment of the present application is preferably one or more of hard carbon, soft carbon, artificial graphite, natural graphite, mesophase carbon microbeads, and lithium titanate.
[0068] In a specific embodiment, the conductive additive of the embodiment of the present application is preferably one or more of carbon nanotubes, acetylene black, Super P, Ketjen black, MXene and graphene.
[0069] In a second aspect, an embodiment of the present application provides a method for preparing the dry electrode film according to the first aspect, the preparation method comprising:
[0070] Mixing an electrode active material, an auxiliary agent, a conductive additive and polyethylene to obtain a first mixture;
[0071] heating the first mixture to obtain a heated first mixture;
[0072] mixing the heated first mixture with polytetrafluoroethylene to obtain a second mixture;
[0073] The second mixture is rolled, and a current collector is added for thermal compounding to obtain a dry electrode membrane.
[0074] The preparation method provided in the embodiment of the present application adds different types of polyethylene (low-density polyethylene, high-density polyethylene, ultra-molecular-weight polyethylene with a molecular weight of 4.5-5 million, and ultra-molecular-weight polyethylene with a molecular weight greater than 9 million). This is because the viscoelasticity of polytetrafluoroethylene is limited, and it cannot ensure sufficient adhesion strength between the active material, the conductive carbon and the current collector, which will cause the active material to break and fall off during the volume expansion / contraction process, reducing the battery capacity and cycle stability. In addition, through electrochemical reduction defluorination, polytetrafluoroethylene is easily converted into carbene carbon (a highly active intermediate with two unbonded electrons on the carbon atom), which then produces conductive sp 2 Hybridized carbon forms a mixed conductive interface, which destroys the stability of the SEI layer by increasing its electronic conductivity. Polyethylene has a fibrillated structure similar to that of polytetrafluoroethylene, and does not contain fluorine atoms in the structure, has stronger reduction stability, and will not destroy the SEI layer on the electrode surface. In addition, ultra-molecular weight polyethylene has a higher degree of polymerization than polytetrafluoroethylene, which also means longer polymer chains, and has better adhesion to active materials, conductive carbon and current collectors, thereby alleviating the breakage and shedding of active materials during volume expansion / contraction, and can effectively improve battery capacity and cycle stability.
[0075] In a specific embodiment, when heating is performed in the embodiment of the present application, the heating temperature is preferably 100-150° C. Among them, when the heating temperature is greater than 150° C., the polyethylene in the first mixture is excessively melted and the fluidity is too high, causing the material to flow and deform during the heating process, resulting in a decrease in the performance of the electrode film; when the heating temperature is less than 100° C., the components in the first mixture are not completely melted or mixed unevenly, resulting in uneven physical and chemical properties inside the electrode film, affecting battery performance.
[0076] In a specific embodiment, when heating is performed in the embodiments of the present application, the heating time is preferably 10-60 minutes.
[0077] In a specific embodiment, the thickness of the dry electrode film of the embodiment of the present application is preferably 60-150 μm. When the thickness of the dry electrode film is greater than 150 μm, the charge transfer distance and resistance increase, the transfer dynamics are poor, and thus the rate performance deteriorates and the capacity is low; when the thickness of the dry electrode film is less than 60 μm, the electrode active material loading is low, and thus the energy density of the battery is low.
[0078] In a specific embodiment, when thermal compounding is performed in the embodiments of the present application, the calendering temperature is preferably 20-120°C.
[0079] It should be noted that the compaction density of the dry electrode membrane in the embodiment of the present application can be 2.3-3.2 g / cm 3 .
[0080] In a specific embodiment, when thermal compounding is performed in the embodiment of the present application, the thermal compounding temperature is preferably 70-150° C. Among them, when the thermal compounding temperature is greater than 150° C., the volatilization or decomposition of components such as additives and adhesives may be accelerated, thereby reducing the adhesion and overall performance of the electrode film; when the thermal compounding temperature is less than 70° C., the temperature is too low and may affect the crystal structure and phase state of the active material in the dry electrode film, thereby affecting the battery performance.
[0081] In a specific embodiment, when thermal compounding is performed in the embodiments of the present application, the thermal compounding time is preferably 10-60 minutes.
[0082] In a third aspect, an embodiment of the present application provides a use of the dry electrode membrane described in the first aspect or the dry electrode membrane prepared by the method described in the second aspect in preparing a battery.
[0083] The technical method of the present application will be further described below in conjunction with specific embodiments.
[0084] The present invention provides a method for preparing a negative electrode sheet, and the specific steps are as follows:
[0085] (1) 800 mg (80 wt%) of lithium titanate (LTO), 40 mg (4 wt%) of octamethylcyclotetrasiloxane, 20 mg (2 wt%) of carboxymethyl cellulose, and 60 mg (6 wt%) of Ketjen black were ground evenly in an agate mortar to form a first mixture.
[0086] (2) The first mixture was placed in a forced air oven, heated to 150° C. in an air atmosphere, and reacted for 30 minutes. Then, 80 mg (8 wt %) of polytetrafluoroethylene was added as a polymer binder to form a second mixture.
[0087] (3) The second mixture was placed on a roller press for rolling, the roller press speed was 2 rpm / min, the rolling temperature was 60°C, and the rolling time was 15 min to form a sheet with a thickness of 100 μm. Then, the roller press speed was adjusted to 1 rpm / min, the temperature was raised to 90°C, and the sheet was rolled and compounded with a 25 μm thick carbon-coated aluminum foil on the roller press for 10 min to obtain a dry negative electrode film.
[0088] (4) The dry-process negative electrode film was cut into LTO negative electrode sheets with a diameter of 12 mm and a thickness of 100 μm, and vacuum dried at 120° C. for 8 h to obtain LTO negative electrode sheets.
[0089] It should be noted that the negative electrode sheets in Examples 1-10 and Comparative Examples 1-2 of the present application all adopt the LTO negative electrode sheets prepared as described above.
[0090] Example 1
[0091] This embodiment 1 provides a method for preparing a dry electrode film 1, and the specific steps are as follows:
[0092] (1) 800 mg (80 wt%) of lithium manganate (LMO), 40 mg (4 wt%) of octamethylcyclotetrasiloxane, 18 mg (1.8 wt%) of carboxymethyl cellulose, 90 mg (9 wt%) of Ketjen black, 10 mg (1 wt%) of carbon nanotubes, and 21 mg (2.1 wt%) of ultra-molecular weight polyethylene (UNMWPE (>9 million)) with a molecular weight greater than 9 million were ground evenly in an agate mortar to form a first mixture.
[0093] (2) The first mixture was placed in a forced air oven, heated to 150° C. in an air atmosphere, and reacted for 30 minutes. Then, 21 mg (2.1 wt %) of polytetrafluoroethylene (PTFE) was added as a polymer binder to form a second mixture.
[0094] (3) The second mixture was placed on a roller press for rolling, with a roller press speed of 2 rpm / min, a rolling temperature of 60°C, and a rolling time of 15 min to form a sheet with a thickness of 100 μm. Then, the roller press speed was adjusted to 1 rpm / min, the temperature was raised to 90°C, and the sheet was rolled and compounded with a 25 μm thick carbon-coated aluminum foil on the roller press for 10 min to obtain a dry electrode membrane 1.
[0095] Example 2
[0096] This embodiment 2 provides a method for preparing a dry electrode film 2, and the specific steps are as follows:
[0097] The dry electrode membrane 2 was prepared according to the method of Example 1, except that the polyethylene was low-density polyethylene (LDPE).
[0098] Example 3
[0099] This embodiment 3 provides a method for preparing a dry electrode film 3, and the specific steps are as follows:
[0100] A dry electrode membrane 3 was prepared according to the method of Example 1, except that the polyethylene was high-density polyethylene (HDPE).
[0101] Example 4
[0102] This embodiment 4 provides a method for preparing a dry electrode film 4, and the specific steps are as follows:
[0103] The dry electrode membrane 4 was prepared according to the method of Example 1, except that the polyethylene was ultra molecular weight polyethylene (UNMWPE (>4-4.5 million)) with a molecular weight of 4-4.5 million.
[0104] Example 5
[0105] This embodiment 5 provides a method for preparing a dry electrode film 5, and the specific steps are as follows:
[0106] The dry electrode membrane 5 was prepared according to the method of Example 1, except that the amount of supramolecular polyethylene with a molecular weight greater than 9 million was 28 mg (2.8 wt %), and the amount of polytetrafluoroethylene was 14 mg (1.4 wt %).
[0107] Example 6
[0108] This embodiment 6 provides a method for preparing a dry electrode film 6, and the specific steps are as follows:
[0109] The dry electrode membrane 6 was prepared according to the method of Example 1, except that the amount of supramolecular polyethylene with a molecular weight greater than 9 million was 10.5 mg (1.05 wt%), and the amount of polytetrafluoroethylene was 31.5 mg (3.15 wt%).
[0110] Example 7
[0111] This embodiment 7 provides a method for preparing a dry electrode film 7, and the specific steps are as follows:
[0112] (1) 850 mg (85 wt%) of NCM811, 100 mg (10 wt%) of Ketjen black, 10 mg (1 wt%) of carbon nanotubes, and 25 mg (2.5 wt%) of ultra-molecular weight polyethylene with a molecular weight greater than 9 million are ground evenly in an agate mortar to form a first mixture.
[0113] (2) The first mixture was placed in a forced air oven, heated to 150° C. in an air atmosphere, and reacted for 30 minutes. Then, 25 mg (2.5 wt %) of PTFE was added as a polymer binder to form a second mixture.
[0114] (3) The second mixture was placed on a roller press for rolling at a speed of 2 rpm / min, a rolling temperature of 60°C, and a rolling time of 15 min to form a sheet with a thickness of 100 μm. Then, the speed of the roller press was adjusted to 1 rpm / min, the temperature was raised to 90°C, and the sheet was rolled and laminated with a 25 μm thick carbon-coated aluminum foil on the roller press for 10 min to obtain a dry electrode film 6.
[0115] Comparative Example 1
[0116] This comparative example 1 provides a method for preparing a dry electrode film 8, and the specific steps are as follows:
[0117] A dry electrode membrane 8 was prepared according to the method of Example 1, except that polyethylene was not added and the amount of polytetrafluoroethylene added was 42 mg (4.2 wt %).
[0118] Comparative Example 2
[0119] This comparative example 2 provides a method for preparing a dry electrode film 9, and the specific steps are as follows:
[0120] A dry electrode membrane 9 was prepared according to the method of Example 7, except that polyethylene was not added and the amount of polytetrafluoroethylene added was 50 mg (5 wt %).
[0121] In order to verify the influence of the dry electrode films 1-6 and 8 prepared in the above-mentioned Examples 1-6 and Comparative Example 1 on the battery performance, the present application provides a method for preparing a button-type lithium-ion battery, and the specific steps are as follows:
[0122] (1) The prepared dry electrode film was cut into LMO positive electrode sheets with a diameter of 10 mm and a thickness of 100 μm, and vacuum dried at 120° C. for 8 h.
[0123] (2) The LMO positive electrode sheet and the LTO negative electrode sheet with a thickness of 100 μm were separated by a 25 μm thick Gelgard 2400 separator (i.e., a polypropylene PP single-layer structure), and 1 mol / L LiPF 6 A mixed solution is used as an electrolyte, wherein the mixed solution consists of ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1.
[0124] (3) After assembling in a glove box filled with argon, the assembled battery was placed under a hydraulic press and pressurized to 50 MPa to obtain a button-type lithium-ion battery.
[0125] In order to verify the influence of the dry electrode films 7 and 9 prepared in the above-mentioned Example 7 and Comparative Example 2 on the battery performance, the present application example provides another method for preparing a button-type lithium-ion battery, and the specific steps are as follows:
[0126] (1) The prepared dry electrode film was cut into NCM811 positive electrode sheets with a diameter of 10 mm and a thickness of 100 μm, and vacuum dried at 120°C for 8 h.
[0127] (2) The NCM811 positive electrode sheet and the 400 μm thick negative electrode lithium sheet were separated by a 25 μm thick Gelgard2325 separator (i.e., a three-layer structure of polypropylene PP / polyethylene PE / polypropylene PP). 6 A mixed solution is used as an electrolyte, wherein the mixed solution consists of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1.
[0128] (3) After assembling in a glove box filled with argon, the assembled battery was placed under a hydraulic press and pressurized to 50 MPa to obtain a button-type lithium-ion battery.
[0129] It should be noted that the dry electrode membrane in the above step (1) is any one of the dry electrode membranes 1-9 prepared in Example 1-7 and Comparative Example 1-2, and correspondingly, a button-type lithium-ion battery 1-9 is obtained.
[0130] The positive electrode electrochemical performance test of the button lithium-ion batteries 1-9 was carried out, and the test voltage window was 2.0-4.3V (vs Li / Li + ), continuous charge and discharge test was carried out at 1C rate current, such as Figure 2 Table 1 shows the electrochemical properties of button-type lithium-ion batteries corresponding to Examples 1-7 and Comparative Examples 1-2.
[0131] Table 1 Electrochemical properties of button-type lithium-ion batteries of Examples 1-7 and Comparative Examples 1-2
[0132]
[0133]
[0134] As can be seen from Table 1, the addition of polyethylene improves the first-cycle specific capacity of the battery and also enhances the cycle stability of the battery. Excellent electrochemical performance is demonstrated for both lithium manganese oxide (LMO) positive electrode and NCM811 positive electrode. It can be seen that the addition of super molecular weight polyethylene is beneficial to the performance of the capacity of the electrode active material and the cycle stability of the battery, and the larger the molecular weight, the better its electrochemical performance. However, by comparing Example 1 with Example 5, it can be seen that the ratio of super molecular weight polyethylene to polytetrafluoroethylene is not the larger the better, and only under a certain appropriate ratio can the electrochemical performance of the electrode and the battery be better improved.
[0135] In order to verify the electrochemical performance of the dry electrode membrane prepared in the examples of the present application for preparing batteries, the button-type lithium-ion batteries of Examples 1-7 and Comparative Examples 1-2 were characterized. The results are as follows: Figures 1 to 3 As shown. Among them, Figure 1 It is a charge and discharge cycle test diagram of button-type lithium-ion batteries prepared in Example 1, Example 4 and Comparative Example 1; Figure 2 It is a charge and discharge cycle test diagram of button-type lithium-ion batteries prepared in Example 1, Example 5 and Example 6; Figure 3 It is a charge and discharge cycle test chart of the button-type lithium-ion batteries prepared in Example 7 and Comparative Example 2.
[0136] according to Figure 1 It can be seen that the addition of ultra-molecular weight polyethylene is beneficial to improving the battery specific capacity and cycle stability, and the larger the molecular weight of polyethylene, the more significant the electrochemical performance of the battery.
[0137] according to Figure 2 It can be seen that the larger the ratio of ultra-molecular weight polyethylene to polytetrafluoroethylene, the better. Only the appropriate ratio can better improve the performance of electrodes and batteries.
[0138] according to Figure 3 It can be seen that ultra-molecular weight polyethylene also improves the performance of NCM811 positive electrode active materials.
[0139] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A dry electrode membrane, characterized in that: Including electrode active materials, additives, conductive additives, polymer binders and current collectors; The polymer binder includes polytetrafluoroethylene and polyethylene, and the polyethylene includes at least one of super molecular weight polyethylene with a molecular weight of 4-4.5 million and super molecular weight polyethylene with a molecular weight greater than 9 million; The auxiliary agent includes at least one of a siloxane crosslinking agent and carboxyl cellulose; The current collector comprises at least one of a carbon-coated aluminum foil and a carbon-coated copper foil; The electrode active material includes at least one of a positive electrode active material and a negative electrode active material; Wherein, the siloxane crosslinking agent includes octamethylcyclotetrasiloxane; the carboxyl cellulose includes carboxymethyl cellulose; The mass ratio of the polytetrafluoroethylene to the polyethylene is 1:1; The electrode active material is 80-85wt%, the conductive additive is 5-10wt%, the polymer binder is 0.5-6wt%, the siloxane crosslinker is (0-5wt%), and the carboxyl cellulose is (0-5wt%).
2. The dry electrode membrane according to claim 1, characterized in that: The positive electrode active material includes LiCoO2, LiMnO2, LiNiO2, LiFePO4, LiMn2O4, LiNiCoAlO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2 and LiNi 0.8 Co 0.1 Mn 0.1 One or more of O2; And / or, the negative electrode active material includes one or more of hard carbon, soft carbon, artificial graphite, natural graphite, mesophase carbon microbeads, and lithium titanate.
3. The dry electrode membrane according to claim 1, characterized in that: The conductive additive includes one or more of carbon nanotubes, acetylene black, Super P, Ketjen black, MXene and graphene.
4. A method for preparing a dry electrode membrane according to any one of claims 1 to 3, characterized in that: include: Mixing an electrode active material, an auxiliary agent, a conductive additive and polyethylene to obtain a first mixture; heating the first mixture to obtain a heated first mixture; mixing the heated first mixture with polytetrafluoroethylene to obtain a second mixture; The second mixture is rolled, and a current collector is added for thermal compounding to obtain a dry electrode membrane.
5. The method for preparing a dry electrode membrane according to claim 4, characterized in that: When the first mixture is heated, the heating temperature is 100-150° C.; and / or, the heating time is 10-60 min; And / or, the thickness of the dry electrode film is 60-150 μm.
6. The method for preparing a dry electrode membrane according to claim 4, characterized in that: When the second mixture is calendered and a current collector is added for thermal compounding, the calendering temperature is 20-120° C.; and / or, the thermal compounding temperature is 70-150°C; And / or, the thermal compounding time is 5-60 minutes.
7. Use of the dry electrode membrane according to any one of claims 1 to 3 or the dry electrode membrane prepared by the method according to any one of claims 4 to 6 in preparing a battery.
Citation Information
Patent Citations
Dry energy storage device electrode and methods of making the same
CN106463267A
High-cycle dry-method electrode membrane, battery pole piece, preparation method and lithium battery
CN116247216A